eCM 2007
DOI: 10.22203/ecm.v013a03
|View full text |Cite
|
Sign up to set email alerts
|

A model of synovial fluid lubricant composition in normal and injured joints

Abstract: The synovial fluid (SF) of joints normally functions as a biological lubricant, providing low-friction and low-wear properties to articulating cartilage surfaces through the putative contributions of proteoglycan 4 (PRG4), hyaluronic acid (HA), and surface active phospholipids (SAPL). These lubricants are secreted by chondrocytes in articular cartilage and synoviocytes in synovium, and concentrated in the synovial space by the semi-permeable synovial lining. A deficiency in this lubricating system may contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 92 publications
1
87
1
7
Order By: Relevance
“…As transport of HA out of SF occurs through the voids of the synovium extracellular matrix, 8,50 alterations in the tissue structure or in the MW of secreted HA might affect the rate that HA permeates the tissue and is lost from SF. The effect of cytokine-regulated alterations in the size distribution of HA may be magnified by size-dependent retention properties of the synovium, with low MW forms of HA being lost quickly from SF and high MW forms being selectively retained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As transport of HA out of SF occurs through the voids of the synovium extracellular matrix, 8,50 alterations in the tissue structure or in the MW of secreted HA might affect the rate that HA permeates the tissue and is lost from SF. The effect of cytokine-regulated alterations in the size distribution of HA may be magnified by size-dependent retention properties of the synovium, with low MW forms of HA being lost quickly from SF and high MW forms being selectively retained.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] The synthesis rate of these lubricating molecules and the molecular weight (MW) of molecules synthesized are important because the balance between the rate of synthesis and the rate of loss of these molecules, by degradation and transport through the semipermeable synovium, dictates their concentration in SF. 7,8 In naturally occurring or animal models of osteoarthritis (OA), rheumatoid arthritis (RA), and injury, the concentrations of HA and PRG4 in SF are often decreased, as is the MW of HA. [9][10][11][12][13] However, the volume of SF is often increased to an even greater extent, 9,14,15 resulting in an overall increase in lubricant content in SF, and complicating assessments of lubricant production and degradation.…”
Section: Introductionmentioning
confidence: 99%
“…HA, lubricin, and possibly phospholipids are the lubricants in synovial fluid 23,39,40 . Human and animal studies have shown that HA and phospholipids reduce tendon gliding resistance and adhesions, without interfering with tendon healing 18,25,41,42 .…”
mentioning
confidence: 99%
“…29 The in vivo environment should be more favorable yet, since human synovial fluid is an excellent lubricant, regardless of the bearing material used. 30,31 Studies on the tribological behavior of ceramics have shown that the wear mechanisms depend on contact conditions during laboratory testing. In most structural ceramics such as silicon nitride, wear occurs through a small-scale surface fracture process if the contact load exceeds a threshold value specific to that material.…”
Section: Tribological Properties Of Silicon Nitridementioning
confidence: 99%